Cell junction protein armadillo repeat gene deleted in velo-cardio-facial syndrome is expressed in the skin and colocalizes with autoantibodies of patients affected by a new variant of endemic pemphigus foliaceus in Colombia - Abreu-Velez, Ana Maria; Yi, Hong; Howard, Michael S. (Dermatology Practical & Conceptual, 2017)
Background: We previously described a new variant of endemic pemphigus foliaceus in El Bagre, Colombia, South America (El Bagre-EPF, or pemphigus Abreu-Manu). El Bagre-EPF differs from other types of EPF clinically, epidemiologically, immunologically and in its target antigens. We reported the presence of patient autoantibodies colocalizing with armadillo repeat gene deleted in velo-cardio-facial syndrome (ARVCF), a catenin cell junction protein colocalizing with El Bagre-EPF autoantibodies in the heart and within pilosebaceous units along their neurovascular supply routes. Here we investigate the presence of ARVCF in skin and its possibility as a cutaneous El Bagre-EPF antigen.Methods: We used a case-control study, testing sera of 45 patients and 45 controls via direct and indirect immunofluorescence (DIF/IIF), confocal microscopy, immunoelectron microscopy and immunoblotting for the presence of ARVCF and its relationship with El Bagre-EPF autoantibodies in the skin. We also immunoadsorbed samples with desmoglein 1 (Dsg1) ectodomain (El Bagre-EPF antigen) by incubating with the positive ARVCF samples from DIF and IIF. Results: ARVCF was expressed in all the samples from the cases and controls. Immunoadsorption with Dsg1 on positive ARVCF immunofluorescence DIF/IIF cases showed that the immune response was present against non-desmoglein 1 antigen(s). Overall, 40/45 patients showed colocalization of their autoantibodies with ARVCF in the epidermis; no controls from the endemic area displayed colocalization. Conclusions: We demonstrate that ARVCF is expressed in many areas of human skin, and colocalizes with the majority of El Bagre-EPF autoantibodies as a putative antigen.